Analisis Dan Perancangan Sistem Informasi Persediaan Obat Pada RSUD H. Abdul Manap Kota Jambi - Sutopo, Sutopo; Devitra, Joni (LPPM Universitas Dinamika Bangsa, 2021)
The rapid development of information technology today in line with the discovery and development of science in the field of information such as computerized information systems. The application of computerized information systems is used in almost all fields including the Hospital. Currently H. Abdul Manap Regional Hospital drug supply management is still done manually, not using information systems technology that is by recording in stock cards yet. The purpose of this study was to analyze the design of drug supply information systems, drug reception, drug demand, drug distribution, drug use, and report recording, the methodology used is system modeling using UML (Unified Modeling Language) which consists of Use Case Diagrams, Activity Diagram and Class Diagram, with prototype design. This research produced a prototype of drug supply information system that could manage computerized drug supply data and could present drug reports that are needed every day or every month. This prototype system still needed to be communicated with the users so that it could be applied to the H. Abdul Manap Regional Hospital of Jambi City to support the entire business process of the drug supply information system at the H. Abdul Manap Regional Hospital of Jambi City.